Method for selection of project management approach based on fuzzy concepts - Kononenko, Igor Vladimirovich; Lutsenko, Svetlana Yuryevna (NTU "KhPI", 2017)
Literature analysis of works that devoted to research of the selection a project management approach and development of effective methods for this problem solution is given. Mathematical model and method for selection of project management approach with fuzzy concepts of applicability of existing approaches are proposed. The selection is made of such approaches as the PMBOK Guide, the ISO21500 standard, the PRINCE2 methodology, the SWEBOK Guide, agile methodologies Scrum, XP, and Kanban. The number of project parameters which have a great impact on the result of the selection and measure of their impact is determined. Project parameters relate to information about the project, team, communication, critical project risks. They include the number of people involved in the project, the customer's experience with this project team, the project team's experience in this field, the project team's understanding of requirements, adapting ability, initiative, and others. The suggested method is considered on the example of its application for selection a project management approach to software development project.

Пропонуються математична модель та метод вибору підходу до управління проектом з урахуванням нечіткості уявлень щодо застосовності існуючих підходів. Вибір здійснюється з таких підходів як: PMBOK, ISO21500, PRINCE2, SWEBOK, Scrum, XP, Канбан. Виділено ряд параметрів проекту, що впливають на результат вибору, та визначено степінь їх впливу. Розглянуто приклад застосування запропонованого методу для вибору підходу до управління проектом з розробки програмного забезпечення.
Метод вибору підходу до управління проектами на основі нечітких уявлень
Keywords: project management approach; selection; fuzzy concepts; model; method; example; управління проектом; підхід; вибір; нечіткі уявлення; модель; метод; приклад